Phylogenetic relationships within the genus Desmothrips (Thysanoptera, Aeolothripidae), an Australian genus of facultative flower-living predators - Pereyra, Veronica Valeria (2010)
A phylogenetic analysis of the Australian Aeolothripidae genus Desmothrips Hood is presented. A data matrix with 27 species is analysed under parsimony criteria. The monophyly of Desmothrips is recovered. Continuous and discrete characters were analysed separately and in combination, and continuous characters were rescaled and analysed under equal weights. Three new species from the northwestern and one from the southeastern areas of Australia are described and illustrated. A key to the 18 species of Desmothrips is provided. © 2010 The Authors. Journal compilation © 2010 The Royal Entomological Society.